1977
DOI: 10.1002/1098-2337(1977)3:1<77::aid-ab2480030107>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Isolation-induced social pecking in domestic chicks: Contemporary correlates and sequelae

Abstract: Aspects of the social pecking of domestic chicks in a free response situation were examined in a series of experiments. It was proposed that a dual pattern of responses involving (a) a preponderance of pecks at the head of a conspecific, and (b) heightened emotionality (as indicated by the emission of distress calls) might be taken to reflect an aggressive tendency, and evidence was reviewed that showed that a brief period of isolation was a sufficient condition to elicit such a pattern. The main questions ask… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1978
1978
1981
1981

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Studies with mice parallel the rat literature (Fredericson, 1952;Rowe & Edwards, 1971), and a set of researches indicates that the components or patterns of aggressive displays in certain fishes are not uniformly influenced by experiential and environmental factors (Clayton & Hinde, 1968;Davis, 1975;Shapiro & Schuckman, 1971). Further, success in peck exchanges between young chicks does not correlate with their success in limited access tests (Rajecki, Nerenz, Barnes, Ivins, & Rein, 1977). Taken together, this growing body of evidence suggests that in the study of any species it may be necessary to forego the assumption that there is some unitary factor in all modes of aggression.…”
Section: University Of Wisconsin-madisonmentioning
confidence: 98%
“…Studies with mice parallel the rat literature (Fredericson, 1952;Rowe & Edwards, 1971), and a set of researches indicates that the components or patterns of aggressive displays in certain fishes are not uniformly influenced by experiential and environmental factors (Clayton & Hinde, 1968;Davis, 1975;Shapiro & Schuckman, 1971). Further, success in peck exchanges between young chicks does not correlate with their success in limited access tests (Rajecki, Nerenz, Barnes, Ivins, & Rein, 1977). Taken together, this growing body of evidence suggests that in the study of any species it may be necessary to forego the assumption that there is some unitary factor in all modes of aggression.…”
Section: University Of Wisconsin-madisonmentioning
confidence: 98%
“…The chicks were hatched communally and were transported in perforated chick cartons. Prior research with hatchlings has revealed that isolation produces com-*Intersubject pecking in hatchlings has been attributed to an aggressive motivation by a number of writers based o n a) the force of the peck [ducklings: Hoffman et al, 19741 ; the reaction of the recipient of the peck [ducklings: Hoffman and Boskoff, 1972;Hoffman et al, 19751 ; and c) peck locus [chicks: Rajecki et al, 1976;Rajecki, Nerenz et al, 1977;Rajecki et al, 19781. Further, recent data from our kdboratory indicates that d) in chicks and poults there are qualitative differences in vocalizations emitted during bouts of voluntary exploration of a novel test area (which included many pecks at the physical environment), compared with aggressive encounters wherein the hatchlings pecked predominantly at the head of their opponent [Rajecki et al, in preparation]. parable patterns and levels of social pecking in chicks with or without brief prior visual and tactile contact with broodmates [cf.…”
Section: Experiments 1 Methodsmentioning
confidence: 99%